Nilai-nilai Pendidikan, Kepemimpinan, dan Strategi Penaklukan Konstantinopel Sultan Muhammad Al-Fatih - Niswar, M; Yulmiati, Yulmiati; Pakasi, Mimit; Ridwan, Ridwan (JPPI (Jurnal Pendidikan Islam Pendekatan Interdisipliner), 2025)
This article explores the educational values, leadership traits, and strategy of Sultan Muhammad Al-Fatih in the conquest of Constantinople. Using a historical method with primary sources from Felix Y. Siauw and Mulkul Farisa Nalva, the study reveals Al-Fatih’s embodiment of Islamic moral and character values such as honesty, responsibility, iffah, and syaja’ah. His leadership reflected vision, justice, and intellectual discipline, aligned with Idealized Influence and Intellectual Stimulation. His strategic conquest demonstrated long-term planning and transformational leadership. These findings offer insights relevant to Islamic education rooted in exemplary leadership.